Business Development Strategies for Processing Derivatives of Non-Timber Forest Products Pine Resin in Groups of Tappers in West Sumatra Province - Bani Safari; Faroby Falatehan; Amzul Rifin (Jurnal Penelitian Pendidikan IPA, 2025)
West Sumatra Province has pine forest areas that have not been maximized as regional economic potential in increasing community income. The study was conducted to analyze the current state of the pine resin NTFP utilization business and the feasibility analysis of the pine resin NTFP derivative product processing business. For the development and improvement of a sustainable regional economy, a processing business development strategy is needed by analyzing related internal and external factors and formulating priority strategies for developing pine resin NTFP derivative processing businesses. The research method is using quantitative and descriptive qualitative analysis using IE Matrix analysis, SWOT analysis, and QSPM analysis to obtain strategic priorities. The analysis data used are primary and secondary data. The results of the study showed that the utilization and processing of pine resin NTFPs is feasible to run with a positive NPV of IDR 10,090,058,000 with an investment of IDR 6,108,024,000, IRR 55%, and Gross B/C 1.23. The resulting strategic priority is the diversification of pine resin products to increase added value. The conclusion of the study is that the utilization and processing of pine resin NTFPs plays a strategic role in supporting economic development in West Sumatra Province